Efek Komposisi Sektoral Pertumbuhan Ekonomi Terhadap Kemiskinan di Riau - Dahlan Tampubolon; Cut Endang Kurniasih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The study of economic growth and poverty is one of the main research themes of today’s social economics and development. This study analyzes the decomposition of different total and sectoral growth effects on poverty. The study was conducted in Riau Province, covering 12 regions with time-series data between 2017-2020 as panel data. Analysis of the effect of sectoral economic growth on poverty using the models of Ravallion and Datt (1996) and Christiaensen et al. (2011). All regression estimates use fixed effect and random effects estimators. The estimation results revealed that labor productivity and expansion of labor force reduce poverty in Riau by 3.82% and 2.85% in the agricultural sector, respectively, while 0.10% and 1.97% in the non-agricultural sector. Agricultural sector are likely to have higher effect of labor productivity and labor force expansion than the non-agricultural sector. Eventually, based on research findings, this study offers some policy for alleviating poverty: encourage higher growth in the agricultural sector and other sectors that are closely related to the agricultural sector and characterized by high pro-poor potential, in this case the trade sector, agricultural product processing industry and transportation services. In addition, it is necessary to create better job opportunities in order to provide employment opportunities in the formal sector considering that the informal sector is often a transitional sector for unskilled and semi-skilled agricultural sector labor, which in turn increase the living standard of people and reduce poverty